Política ambiental e desenvolvimento urbano na serra do periperi em Vitória da conquista - BA - Benedictis, Nereida Maria Santos Mafra (2007)
﻿This present dissertation has as its aim of study an analysis of the environmental policy and the urban development at the Periperi Hill. Such analysis arose due to concerns related to the disordered occupation in that Hill and also due to the environmental problems caused by this occupation. By opening roads and developing areas for housing and mineral extraction activities, man has altered considerably the landscape natural balance in that hill and caused among other difficulties, grave environmental problems, such as the erosin at the hill coast, deforestation, obstruction and pollution of the Verruga River. Therefore, in 1998 it was decreed by the Municipal Public Power that Periperi Hill became an Environmental Preservation Area with a Unit of Conservation known as Periperi Hill Municipal Park, an environmental policy implemented at the Hill that aims to hinder this occupation and to protect areas that are of great environmental importance to the city. It looking at what is now exposed and aiming to consider the Periperi Hill s environmental policy and the relationship of the occupation process, that this present work has the objective of understanding how the expansion of the city s urban network in Vitória da Conquista BA and the mineral activities cause an influence in the process of environmental degradation at the Periperi Hill